The dispersion and detection patterns of mtDNA‐assigned red fox Vulpes vulpes scats in Tasmania are anomalous. Issue 4 (6th June 2014) - Marks, Clive A; Obendorf, David; Pereira, Filipe; Edwards, Ivo; Hall, Graham P; Lukacs, Paul
Summary Models used for resource allocation in eradication programmes must be based on replicated data of known quality and have proven predictive accuracy, or they may provide a false indication of species presence and/or distribution. In the absence of data corroborating the presence of extant foxes Vulpes vulpes in Tasmania, a habitat‐specific model based upon mtDNA data (Sarre et al. 2012. Journal Applied Ecology, 50, 459–468) implied that foxes were widespread. Overall, 61 of 9940 (0·6%) surveyed scats were assigned as mtDNA fox positive by the fox eradication programme (FEP). We investigated the spatiotemporal distribution of the 61 mtDNA‐assigned fox scats and modelled the probability of replicating scat detection in independent surveys using detection dogs based upon empirically derived probabilities of scat detection success obtained by the FEP using imported fox scats. In a prior mainland study, fox genotypes were recurrently detected in a consecutive four‐day pool of scats. In Tasmania, only three contemporaneously collected scat pairs of unknown genotype were detected by the FEP within an area corresponding to a conservatively large mainland fox home range (639 ha) in a decade. Nearest neighbour pairs were widely spaced (mean = 7·0 km; circular area = 153 km2) and generated after a mean of 281 days. The majority of assigned mtDNA positive scats were found in urban and peri‐urban environments corresponding to small mainland fox home ranges (30–45 ha) that imply higher scat density and more certain replication. Using the lowest empirically determined scat detection success for dogs, the failure to replicate fox scat detection on 34 of 36 occasions in a large (639 ha) home range is highly improbable (P = 0·00001) and suggestive of Type I error. Synthesis and applications. Type I error, which may have various sources, should be considered when scat mtDNA data are few, accumulated over many years, uncorroborated by observations of extant specimens, inadequately replicated in independent surveys within an expected spatiotemporal scale and reported in geographically isolated environments unlikely to have been colonized.